2007
DOI: 10.3844/jssp.2007.106.116
|View full text |Cite
|
Sign up to set email alerts
|

Ten Common Misunderstandings, Misconceptions, Persistent Myths and Urban Legends about Likert Scales and Likert Response Formats and their Antidotes

Abstract: Abstract:A recent article by Jamieson in Medical Education outlined some of the (alleged) abuses of "Likert scales" with suggestions about how researchers can overcome some of the (alleged) methodological pitfalls and limitations [1] . However, many of the ideas advanced in the Jamison article, as well as a great many of articles it cited, and similar recent articles in medical, health, psychology, and educational journals and books, are themselves common misunderstandings, misconceptions, conceptual errors, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
497
0
26

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 725 publications
(526 citation statements)
references
References 24 publications
3
497
0
26
Order By: Relevance
“…The values of emodiversity are produced by the use of invalid arithmetic 188 interval data when summed and averaged (Carifio & Perla, 2007), the act of dividing an 197…”
Section: Part 1: Numerical Analyses Of the Effects Of Bounded Richnesmentioning
confidence: 99%
“…The values of emodiversity are produced by the use of invalid arithmetic 188 interval data when summed and averaged (Carifio & Perla, 2007), the act of dividing an 197…”
Section: Part 1: Numerical Analyses Of the Effects Of Bounded Richnesmentioning
confidence: 99%
“…Because of the absence of a more precise measure (e.g., a ruler) it is possible to operationalize a continuous measurement (a 100-mm line) using an ordinal scale with seven anchored points, for attitude affirmations or as derived phrases of semantic differential (17) .…”
Section: Rev Esc Enfermmentioning
confidence: 99%
“…The response categories in Likert scales have a rank order, but the intervals between values cannot be presumed equal (23) . However, other authors contest this claim (17,21) . They report that this article, and the references cited in the article, suffers from misunderstandings and gross errors based on myths, not true and conceptual errors in Likert scales.…”
Section: Rev Esc Enfermmentioning
confidence: 99%
“…Nevertheless, its usefulness presents some drawbacks as it has been pointed out, for instance, in [1,4,11,14,23]. In the literature some authors have suggested to establish a correspondence between each Likert response category and a fuzzy value chosen from a class of flexible fuzzy sets previously stated by experts (see, for instance, [16,17]).…”
Section: Introductionmentioning
confidence: 99%